Malaysian fungal endophytes as a source of bioactive metabolites / Hamidah Abu Bakar - Abu Bakar, Hamidah (2009)
Endophytes are microorganisms that reside within plants and appear as an enormous yet relatively untapped source of natural product. The objectives of this study include isolation of endophytes from medicinal plants, determination of antimicrobial and antitumour activity of cultures extracts, identification of the bioactive endophytes through morphological, biochemical and genetic characterization. A total number of 348 endophytes were isolated through surface sterilization from 24 local medicinal plants of the Kuala Pilah Rain Forest, Malaysia. For the antimicrobial test, a disc diffusion assay was employed and the endophytic crude extracts were tested against bacteria (Bacillus subtilis, Micrococcus luteus, Staphylococcus aureus and Escherichia coli) and fungi (Candida albicans, Aspergillus niger, and Saccharomyces cerevisiae).